Sputum and BAL Clara cell secretory protein and surfactant protein D levels in asthma. Issue 6 (18th March 2015) - Emmanouil, P.; Loukides, S.; Kostikas, K.; Papatheodorou, G.; Papaporfyriou, A.; Hillas, G.; Vamvakaris, I.; Triggidou, R.; Katafigiotis, P.; Kokkini, A.; Papiris, S.; Koulouris, N.; et al.
Abstract: Clara cell secretory protein (CC16) is associated with Th2 modulation. Surfactant protein D (SPD) plays an important role in surfactant homeostasis and eosinophil chemotaxis. We measured CC16 and SPD in sputum supernatants of 84 asthmatic patients and 12 healthy controls. In 22 asthmatics, we additionally measured CC16 and SPD levels in BAL and assessed smooth muscle area (SMA), reticular basement membrane (RBM) thickness, and epithelial detachment (ED) in bronchial biopsies. Induced sputum CC16 and SPD were significantly higher in patients with severe asthma (SRA) compared to mild–moderate and healthy controls. BAL CC16 and SPD levels were also higher in SRA compared to mild–moderate asthma. CC16 BAL levels correlated with ED, while SPD BAL levels correlated with SMA and RBM. Severity represented a significant covariate for these associations. CC16 and SPD levels are upregulated in SRA and correlate with remodeling indices, suggesting a possible role of these biomarkers in the remodeling process.